Intervensi Pemerintah dalam Saham BUMN (Golden Share) dan Relevansinya dengan Pasal 33 UUD 1945 - Zulfaidah, Rena; Oganta, Apre Aldo (Sharia Journal and Education Center Publishing, 2026)
This research examines the juridical position of government intervention through the golden share instrument (Series A Dwiwarna Shares) in State-Owned Enterprises (SOEs) listed on the stock exchange, analyzed from the perspective of Article 33 of the 1945 Constitution, Constitutional Law, and Criminal Law. The primary issue arises when the state's special veto rights conflict with the principle of shareholder equality (one share one vote) and the potential for abuse of power leading to corruption. The research method employed is normative legal research with statutory and conceptual approaches. The results indicate that the golden share is a constitutional instrument to safeguard economic sovereignty as long as its use is restricted to strategic policies concerning public welfare. However, this study finds a legal vacuum regarding the limits of managerial intervention, which often triggers maladministration and systemic losses for public investors. The proposed novelty is the concept of